Prevensi Career Indecision Remaja Pasca Pandemi Melalui Perencanaan Karir Berlandaskan Nilai-Nilai Kearifan Nusantara: Sebuah Narrative Review - Muslihati, Muslihati; Multisari, Widya; Prihatiningsih, Riskiyana; Wulandari, Arifah; Pratiwi, Awalya Siska (Universitas Muria Kudus, 2023)
Preparing for a future career is an important task for adolescents. Technological changes and the pandemic have made many adolescents experience career indecision. Career planning based on local wisdom values is intended to assist adolescents in making appropriate career decisions. This research uses the narrative review method by searching literature from 2014 to 2022 from sources ScienceDirect, SagePub, and Google Scholar. The results of the analysis show that there are local wisdom values that can be integrated into adolescent career planning such as religious, responsibility, hard work/ tenacity, and self-understanding.